Dual-Polarized Synthetic Antenna Array for GNSS Handheld Applications. (16th January 2013) - Dehghanian, V.; Broumandan, A.; Zaheri, M.; Nielsen, J.
Abstract : Small portable Global Navigation Satellite System (GNSS) receivers have revolutionized personal navigation through providing real-time location information for mobile users. Nonetheless, signal fading due to multipath remains a formidable limitation and compromises the performance of GNSS receivers. Antenna diversity techniques, including spatial and polarization diversity, can be used to mitigate multipath fading; however, the relatively large size of the spatially distributed antenna system required is incompatible with the small physical size constraints of a GNSS handheld receiver. User mobility inevitably results in motion of the handset that can be exploited to achieve diversity gain through forming a spatially distributed synthetic array. Traditionally, such motion has been construed as detrimental as it decorrelates the received signal undermining the coherent integration processing gain generally necessary for acquiring weak faded GNSS signals. In this paper the processing gain enhancement resulting from a dual-polarized synthetic array antenna, compatible with size constraints of a small handset that takes advantage of any user imposed motion, is explored. Theoretical analysis and experimental verifications attest the effectiveness of the proposed dual-polarized synthetic array technique by demonstrating an improvement in the processing gain of the GNSS signal acquisition operation.